Elevated Plasma Cyclophillin A in Hemodialysis and Peritoneal Dialysis Patients: a Novel Link to Systemic Inflammation (Iranian Journal of Kidney Diseases, 2017)
Introduction. Cyclophillin A has emerged as a novel mediator of oxidative stress and inflammation and a major player in cardiovascular disease, diabetes mellitus, viral infections, and neurodegenerative and thrombotic disorders. Cyclophillin A is released by certain cell types spontaneously or in response to inflammatory mediators, hypoxia, oxidative stress, and hyperglycemia. Many of these conditions are either present or frequently occur in patients with end-stage renal disease and can stimulate release of cyclophillin A, thereby amplifying systemic inflammation. To our knowledge, the effect of end-stage renal disease and dialysis modalities on circulating cyclophillin A has not been previously investigated. This study tested the hypothesis that extracellular cyclophillin A is elevated in patients maintained on hemodialysis and peritoneal dialysis. Materials and Methods. Cyclophillin A, high-sensitivity C-reactive protein, interleukin-6, tumor necrosis factor-α, and lipid levels were measured in the fasting plasma samples from 20 hemodialysis and 20 peritoneal dialysis patients, and 20 age- and sex-matched controls. Results. Plasma cyclophillin A concentration in the patients on hemodialysis (105.3 ± 6.2 ng/mL) and peritoneal dialysis (106.8 ± 9.0 ng/mL) were significantly higher than that in the control group (29.7 ± 4.1 ng/mL). This was associated with significant elevation of high-sensitivity C-reactive protein, interleukin-6, and tumor necrosis factor-α. Plasma cyclophillin A concentration showed direct correlations with high-sensitivity C-reactive protein, interleukin-6, and tumor necrosis factor-α, and an inverse correlation with high-density lipoprotein cholesterol concentration. Conclusions. Plasma cyclophillin A concentration is markedly elevated and positively correlates with the markers of systemic inflammation in hemodialysis and peritoneal dialysis patients.